Respuesta :

Step by step. :)


STEP
1
:
Equation at the end of step 1
0 - 7n • (n - 7) = 0
STEP
2
:
Equation at the end of step 2
-7n • (n - 7) = 0
STEP
3
:
Theory - Roots of a product
 3.1    A product of several terms equals zero. 

 When a product of two or more terms equals zero, then at least one of the terms must be zero. 

 We shall now solve each term = 0 separately 

 In other words, we are going to solve as many equations as there are terms in the product 

 Any solution of term = 0 solves product = 0 as well.
Solving a Single Variable Equation:
 3.2      Solve  :    -7n = 0 

 Multiply both sides of the equation by (-1) :  7n = 0


Divide both sides of the equation by 7:
                     n = 0
Solving a Single Variable Equation:
 3.3      Solve  :    n-7 = 0 

 Add  7  to both sides of the equation : 
                      n = 7



This is what i got! if i’m wrong i’m so sorry
but i tried. have a amazing day☺️☺️